Evaluation of seasonal variation in the incidences of bacterial infection among surgical patients - Basnet, Robin Bahadur (Journal of General Practice and Emergency Medicine of Nepal, 2011)
Introduction: Although a lot of attention has been paid to the prevention of nosocomial infections, surgical site infections (SSIs) continue to comprise a major proportion of all adverse events in surgical patients. So this study is designed to evaluate the common pathogens prevalent in surgical patients and find its seasonal trend. Method: This is a prospective analytical study of all operated cases in General Surgery Unit III, Bir Hospital from March 2010 to February 2011. Evaluation of bacteriological culture pattern among patients with wound infection 0 to 30 days after the operation was done. Result: There were total of 564 elective and 292 emergency operations. Surgical site infection rate was 12.1%, 18.2%, 12.2% and 10.7% respectively in spring, summer, autumn and winter seasons. Staphylococcus and Enterococcus were the most common gram positive organisms isolated which were lower in colder seasons as compared to the other seasons while gram negative E coli, Acenatobacter, Pseudomonas and Enterobacter showed predominance in the warmer season. Conclusion: If further validated, our findings could have important implications for future infection prevention intervention studies and for choice of empirical antimicrobial therapy among hospitalized adults.